2018
DOI: 10.1166/jnn.2018.15330
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Derived Stem Cells and Osteoblasts Interaction with Fe–Cr–Nb–B Magnetic Nanoparticles

Abstract: The use of materials at nanoscale is currently of increasing interest for life sciences and medicine. Magnetic nanoparticles (MNPs) are under scrutiny for a large array of applications in nanomedicine as diagnostic and therapeutic tools. Proprietary Fe-Cr-Nb-B MNPs display heating properties that recommends them as potent agents for delivery of local hyperthermia for the treatment of solid tumours. Stem cell mediated delivery represents a safe and accurate modality to target remote or metastatic tumour sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Follow-up of the fate of administered stem cells using combined imaging methods has been proposed as a method to discriminate tumorigenic transformation. In the future, this technology can be used to monitor liver cancer after SCT[ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up of the fate of administered stem cells using combined imaging methods has been proposed as a method to discriminate tumorigenic transformation. In the future, this technology can be used to monitor liver cancer after SCT[ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, stem cells have been proposed as suitable carriers for tumor-targeting therapeutics 25 . In our previous work 26 , 27 , we have investigated the interaction of Fe-Cr-Nb-B MPs with human adipose-derived mesenchymal stem cells (MSCs) and human bone marrow-derived MSCs. It was observed that Fe-Cr-Nb-B MPs have been internalized by both types of cells and did not induce in vitro cytotoxicity, indicating a good biocompatibility.…”
Section: Magnetic Particles and Magnetic Ferrofluidmentioning
confidence: 99%
“…Human primary ADSC were obtained from healthy donors undergoing liposuction procedures for cosmetic reasons after institutional board ethical approval and written informed patient consent. Lipoaspirate was processed within 24 hr after surgical procedure as previously described 13 . Briefly, lipoaspirate was washed with PBS, enzymatically digested with collagenase type I (0.01 mg/ml) for 2 hr at 37.5°C, and centrifuged at 300 g for 5 min at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%
“…Excellent biocompatibility, improved proliferation as well as preserved or even increased differentiation potential has been reported for MSC of human origin loaded with MNP of various compositions and coatings 13,14 . Magnetic actuation has been used in testing various remote controlled systems for therapeutic purposes 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation